Impact of Biomarkers of Inflammation and Extracellular Matrix Turnover on the Outcome of Atrial Fibrillation Ablation: Importance of Matrix Metalloproteinase-2 as a Predictor of Atrial Fibrillation Recurrence - OKUMURA, YASUO; WATANABE, ICHIRO; NAKAI, TOSHIKO; OHKUBO, KIMIE; KOFUNE, TATSUYA; KOFUNE, MASAYOSHI; NAGASHIMA, KOICHI; MANO, HIROAKI; SONODA, KAZUMASA; KASAMAKI, YUJI; HIRAYAMA, ATSUSHI (Journal of cardiovascular electrophysiology, 2011)
MMP‐2 Predicts the Outcome of AF Ablation. Introduction: Although catheter ablation can effectively eliminate atrial fibrillation (AF), the progression of atrial remodeling increases the risk of recurrence. AF is associated with inflammation and subsequent myocardial fibrosis. We therefore examined the possibility of determining the postablation prognosis of patients with AF using biomarkers of inflammation and collagen turnover. Methods and Results: Subjects were 50 patients who underwent catheter ablation for drug‐resistant AF. High‐sensitivity CRP (hs‐CRP), interleukin (IL)‐6, carboxyl‐terminal telopeptide of collagen type I (ICTP), metalloproteinase (MMP)‐2, tissue inhibitor of MMP‐2 (TIMP‐2), atrial natriuretic peptide (ANP), and brain natriuretic peptide (BNP) were measured before and 2.2 ± 0.8 months after ablation. During the follow‐up period of 14.0 (4.7–20.9) months, AF recurred in 21 of the 50 patients. Recurrence was associated with an MMP‐2 elevation (860.3 ± 120.8 ng/mL vs 687.0 ± 122.5 ng/mL [in patients without recurrence]), ICTP elevation (3.2 ± 1.1 ng/mL vs 2.7 ± 0.6 ng/mL), BNP elevation, greater body mass index, nonparoxysmal AF, and hypertension (P < 0.05 for all). Serum MMP‐2 and nonparoxysmal AF were shown by multivariate analysis to be independent predictors for postablation AF recurrence. Overall, hs‐CRP, IL‐6, ANP, and BNP levels decreased, and MMP‐2, TIMP‐2, and ICTP levels increased 2 months after ablation. Conclusions: Our finding that markers of collagen turnover were elevated in patients who experienced AF recurrence after ablation indicate that these markers might be a useful guide to identify a subgroup of AF patients who require extensive ablation strategies. A 2‐month postablation elevation in collagen turnover markers suggests that the wound healing process persists for that long after ablation. (J Cardiovasc Electrophysiol, Vol. 22, pp. 987‐993, September 2011)